Perception on the implementation of public private partnership (PPP) in Malaysia - Fatimah Az-Zahra binti Haris (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
Public private partnership (PPP) has been continuously being a preferable procurement mode used by the Government. This present study is conducted to seek the perception of the main PPP contracting parties which are public sector and private sector on how they perceive the PPP implementation in Malaysia. In particular, the perception on the importance of PPP objectives, attractive factors, negative factors, driving forces and value for money (VFM) measures were sought from the respondents. Using a questionnaire survey, 180 completed responses were received representing 72% response rate. The results were then analysed using descriptive statistical tests which include mean and standard deviation. In addition, mean score ranking was also used to rank the factors according to the level of importance. The results show that the top three objectives are 'to enhance private sector involvement in economic development', 'to improve efficiency of public services delivery' and 'to improve privatisation programme'. In relation to the attractive factors for PPP adoption, the top five attractive factors are 'to facilitate innovative approaches', 'solve the problem of public sector budget restraint', 'provide an integrated solution for public infrastructure or services', 'save time in delivering the project' and 'benefit to the local economic development'. The top five negative factors that hinder the adoption of PPP are 'lengthy delay in negotiation', 'lack of government guidelines and procedures on PPP', 'higher charge to direct users', 'lengthy delay because of political debate' and 'confusion over government objectives and evaluation criteria'. The key driving forces for PPP implementation in Malaysia as perceived by the respondents include ‗economic development pressure of demanding more facilities', 'high quality of service required', 'shortage of government funding', 'private incentives' and 'social pressure of poor public facilities'. Finally, the respondents perceived that 'competitive tender', 'private sector technical innovation', 'optimal use of asset/facilities to the public sector', 'efficiency in risk allocation' and 'performance based payment mechanism' as the top five most important measures to enhance VFM achievement from PPP projects in Malaysia. The findings of the present study are of practical significance to policy makers and practitioners of PPP in Malaysia. The study also expects to add to the limited knowledge in this field as PPP implementation is continuously progressing in Malaysia.